Implementation of Baby Massage to Improve Health Degree in Infants: Implementasi Pijat Bayi untuk Meningkatkan Derajat Kesehatan pada Bayi - Khuzaifah, Khuzaifah; Kuswanti, Febty; Longgupa, Lisda Widianti; Nurfatimah, Nurfatimah; Sakti, Putri Mulia; Entoh, Christina; Lailatul K., Marlina Fitriyah; Noya, Fransisca; Sitorus, Sony Bernike Magdalena; Nurmiaty, Nurmiaty; Ramadhan, Kadar (Poltekita: Jurnal Pengabdian Masyarakat, 2025)
The healthy life expectancy at birth in Indonesia was recorded at 3.8. This figure was influenced by the care provided during pregnancy, childbirth, and the neonatal period. The aim of this community service was to deliver optimal midwifery care to infants to enhance sleep quality, alleviate fussiness, boost appetite, and promote weight gain, ultimately improving the overall health status of the infants. The community service activity took place on Friday, November 10, 2023, in Lantojaya village, targeting infants aged 0 to 23 months. The procedures implemented included assessment, planning, action, and evaluation. Among the 12 infants who received baby massage, behavioral changes were observed before and after the intervention: full-body movements increased from 66.7% to 100%; visual attention improved in 91.7% of the infants; non-nutritive sucking rose by 25%; object-holding activity reached 100%; and self-touching behavior was noted in 91.7% of the infants. The conclusion drawn from this community service was that baby massage had a relaxing effect on infants. Therefore, it is recommended that families regularly perform baby massage, either independently or with assistance from healthcare professionals.